Infertility analysis by hysterolaparoscopy - Daddenavar, Archana V.; Daddenavar, Vikas M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysteroscopy provides a means of direct observation of intra-uterine defects, which can eventually interfere with fertility and as a therapy for intra-uterine lesions, for which hysteroscopy is the method of choice. To study the various etiological factors responsible for infertility in females by using hystero-laparoscopy. Methods: Prospective study of patients admitted with diagnosis of infertility in Department of Obstetrics and Gynaecology in S N Medical College, Bagalkot from October 2013-April 2015. Results: Of the 50 cases of infertility, 35 cases (70%) were of primary infertility and 15 cases (30%) were of secondary infertility. Most of the patients (74%) had duration of Infertility of 1–5 years. Various etiological factors detected during study are uterine factors in 12%, tubal factors in 34%, ovarian factors in 18%. Unexplained in 16% of cases. Conclusions: In present study, hysterolaparoscopy helped in diagnosis of certain factors causing infertility which can’t be diagnosed by any other method short of hysterolaparoscopy. Tubal factors were found to be major cause of infertility.